The Śūraṅgama Sūtra, sudden awakening and gradual cultivation in Chan Buddhism during the Tang and Song periods - Gong, Jun (Studies in Chinese Religions, 2023)
This article undertakes an indepth examination of the Śūraṅgama Sūtra’s influence on the ideas of sudden awakening and gradual cultivation in Chan Buddhism during the Tang (618–907) and Song (960–1279) dynasties. It focuses on the complex relationship between the sūtra and these ideas within the meditation teachings of the Shenxiu Lineage 神秀系 of the Northern School and the Heze Lineage 菏澤系 of the Southern School, conducting detailed analysis of their intellectual history and offering a new exploration of connections between Northern Chan and Heze Shenhui’s 菏澤神會 (684–758) ideas about subitism and gradualism. This article also proposes a new interpretation of Chan Śūraṅgama study from the late Tang to the Song in relation to discussions about sudden awakening and gradual cultivation. It points out differences in meditation teachings between the Song and Tang periods with regard to this question, and on this basis examines how such teachings were Sinicised through the incorporation of Tathāgatagarbha scriptures such as the Śūraṅgama, according to different trajectories of intellectual history.